Critical care nursing and emergency response issues - Mohamed Ludin, Salizar (IIUM Press, International Islamic University Malaysia, 2018)
In recent years, there has been a great deal of attention paid to critical care and disaster management and preparing the healthcare system to handle critically ill clients and disasters victims, in particular events. Most of the attention has focused on the first responders and the initial emergency management, depending on the nature of the emergency and disaster. To understand further about problems, gaps and ways to handle these cases, research in this field with a suitable design, methods, instruments, and analyses should be carried out. Findings from these studies will allow us to recommend solutions to performing effective critical care, emergency and pre-hospital critical care activities in much broader areas in the future. In order to fill the gap, this book (a compilation of four studies) is prepared to provide additional knowledge on issues related to Critical Care Nursing and Emergency response and example of the study. This book consists of 4 chapters: Chapter 1 is on Critical Care nurses’ awareness of medication errors and its prevention: a mixed method study; Chapter 2 is on relationship between nurses’ knowledge, attitudes, and practice on delirium with assessment and occurrence of delirium among ICU patients; Chapter 3 is on families' satisfaction on care provided to intensive care unit (ICU) survivors: comparison between ICU and general ward setting in Hospital Tengku Ampuan Afzan, Kuantan Pahang and Chapter 4 is on Emergency response team contribution in flood disaster and experience in building community resilience: a qualitative study. Many thanks goes to all authors and co-authors; Kulliyyah of Nursing and last but not least, International Islamic University Malaysia for approving the studies and this book to be produced for sharing of knowledge.